A Workbook for a Course in Rizal - Fadul, Jose (Quezon City, Philippines : C & E Publishing Inc., 2008)
This workbook is most affectionately dedicated to the Filipino Youth whom Rizal himself sought to inspire with his works.
1. Rizal's Early education (Comics) 2. Rizal's Roots and Relatives (Genogram) 3. Timeline Local and international Perspective 4. A comic Strip by Rizal 5. The events of the early 1880s 6. Symbolism in the cover design of Rizal's First novel 7. Characters in Rizal's novels 8. Rizal's second trip to Europe 9. Tracing Rizal's travels 10. Portions of Rizal's Last poem 11. Interrelating the characters in Rizal's novels 12. Designing Monument 13. Streets of Dapitan 14. Analyzing Rizal's Handwriting 15. Rizal on stamps 16. Rizal's name in Japanese (Learning Katakana)
Includes bibliographical references.
Keywords: RIZAL, JOSE, 1861-1896 -- STUDY AND TEACHING